Analisis Kesalahan Mahasiswa dalam Menyelesaikan Soal Matematika Ditinjau dari Prosedur Newman - Daswarman Daswarman (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
A reason for students’ low learning outcomes in Basic Mathematics 1 in PGSD FKIP Univer sitas Bung Hatta is found to be errors in answering the questions. This study aims to describe the errors and find factors that cause students errorly answer the questions in Basic Mathematics 1. This is a descriptive research using case study design with interview and test as data collection techniques. Errors analysis conducted with Newman Procedures shows that 4.89% of students experience Reading error, 8.22 % of students experience Comprehension Error, 12.67% experience Transformation Error, 15.11% of students experience Process Skill Error, and 1.56% of students experience Encoding Error. Factors that cause errors include abhorrance of math, carelessness in solving problems, reluctance to ask questions during lecture, and the absence of motivation to learn.